Retinal arteriolar geometry is associated with cerebral white matter hyperintensities on MRI - Doubal, F.N.; de Haan, R; MacGillivray, T.J.; Cohn-Hokke, P.; Dhillon, B.; Dennis, M.S.; Wardlaw, J.M. (John Wiley & Sons, 2010)
Background. Cerebral small vessel disease (lacunar stroke and cerebral white matter hyperintensities) is caused by vessel abnormalities of unknown aetiology. Retinal vessels show developmental and pathophysiological similarities to cerebral small vessels and microvessel geometry may influence vascular efficiency. Hypothesis. We hypothesized that retinal arteriolar branching angles or co-efficients (the ratio of the sum of the cross sectional areas of the two daughter vessels to the cross sectional area of the parent vessel at an arteriolar bifurcation) may be associated with cerebral small vessel disease. Methods. We performed a cross-sectional observational study in a tertiary referral hospital, United Kingdom. An experienced stroke physician recruited consecutive patients presenting with lacunar ischaemic stroke with a control group consisting of patients with minor cortical ischaemic stroke. We performed brain magnetic resonance imaging to assess the recent infarct and periventricular and deep white matter hyperintensities. We subtyped stroke with clinical and radiological findings. We took digital retinal photography to assess retinal arteriolar branching co-efficients and branching angles using a semi-automated technique. Results. We recruited 205 patients (104 lacunar stroke, 101 cortical stroke), mean age 68 (Standard Deviation 12) years. With multivariate analysis, increased branching coefficient was associated with periventricular white matter hyperintensities (p=0.006) and ischaemic heart disease (p<0.001); decreased branching co-efficient with deep white matter hyperintensities (p=0.003) but not with lacunar stroke subtype (p=0.96). We found no associations with retinal branching angles. Conclusions. Retinal arteriolar geometry differs between cerebral small vessel phenotypes. More research is needed to ascertain the clinical significance of these findings.
Keywords: white matter hyperintensities; MRI; Cerebral small vessel disease; Retinal vessels; cerebral infarction; factors; ischaemic stroke; leukoaraiosis; risk; stroke